2016
DOI: 10.1530/edm-16-0047
|View full text |Cite
|
Sign up to set email alerts
|

Association of newly diagnosed type 1 diabetes and autoimmune pancreatitis

Abstract: SummaryAutoimmune pancreatitis is a new nosological entity in which a lymphocytic infiltration of the exocrine pancreas is involved. The concomitant onset of autoimmune pancreatitis and type 1 diabetes has been recently described suggesting a unique immune disturbance that compromises the pancreatic endocrine and exocrine functions. We report a case of type1 diabetes onset associated with an autoimmune pancreatitis in a young patient who seemed to present a type 2 autoimmune polyglandular syndrome. This rare a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Therefore, IgG4-RD, especially AIP, is often complicated by ITP. IgG4-RD has also been reported in conjunction with APS-3, but some studies have focused on the complications of AIP and type 1 DM (also associated with Hashimoto's disease) ( 35 , 36 ), while others have discussed the complications of sclerosing cholangitis and type 1 DM (also associated with Hashimoto's disease) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, IgG4-RD, especially AIP, is often complicated by ITP. IgG4-RD has also been reported in conjunction with APS-3, but some studies have focused on the complications of AIP and type 1 DM (also associated with Hashimoto's disease) ( 35 , 36 ), while others have discussed the complications of sclerosing cholangitis and type 1 DM (also associated with Hashimoto's disease) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ennazk et al suggested that cell-mediated autoimmunity could explain the occurrence of AIP and type 1 DM and that individuals carrying HLA DRB1*04:05-DQB1*04:01 are most at risk of complications of AIP and type 1 DM ( 36 , 39 ).…”
Section: Discussionmentioning
confidence: 99%